Mechanistic study of CTHRC1 in promoting Wilms’ tumor progression by regulating M2-type tumor-associated macrophages polarization - Yingquan Zhuo; Xiaoyun Feng; Wenqi Zhang; Jun Du; Xu Sun; Xi Luo; Wei Wang; Hua Jiang; Huajian Gu (Journal of Translational Medicine)
Abstract Background This study aimed to investigate the role of Collagen triple helix repeat protein 1 (CTHRC1) in Wilms’ tumor (WT) progression and elucidate its molecular mechanism in promoting WT malignancy through regulation of M2-type tumor-associated macrophages (M2-TAMs) infiltration and polarization. Methods Bioinformatics analysis was conducted using public databases to examine CTHRC1 expression and immune cell infiltration in WT. Single-cell sequencing was employed to analyze expression patterns of CTHRC1 and M2-TAMs markers. CTHRC1 expression and M2-TAM infiltration were validated in WT tissues using RT-qPCR, Western blot, immunohistochemistry, and immunofluorescence. In vitro and in vivo experiments were performed to investigate the biological functions of CTHRC1 in WT and its effects on M2-TAMs polarization. Transcriptome sequencing and bioinformatics analysis were used to explore potential signaling pathways. The TNFSF9-TNFRSF9 axis was further investigated through neutralizing antibody rescue experiments and co-localization analysis. The role of M2-TAMs in promoting WT progression via the PI3K/AKt pathway was examined using xenograft models and in vitro experiments. Results CTHRC1 and M2-TAMs were significantly overexpressed in WT tissues and positively correlated. CTHRC1 overexpression promoted WT cell proliferation, inhibited apoptosis, and induced M2-TAMs polarization both in vitro and in vivo. Transcriptome analysis revealed that CTHRC1 regulated M2-TAMs polarization through the TNFSF9-TNFRSF9 axis. CTHRC1 overexpression upregulated TNFSF9: expression and secretion in tumor cells, promoting its binding to TNFRSF9 on M2-TAMs. Neutralizing TNFSF9 or knockdown of TNFRSF9 significantly attenuated CTHRC1-induced M2-TAM infiltration and polarization. M2-TAMs promoted WT progression by activating the PI3K/Akt pathway in tumor cells. Inhibition of PI3K/Akt signaling reversed M2-TAM-mediated WT progression. Conclusions CTHRC1 promotes WT progression by inducing M2-TAMs polarization through the TNFSF9-TNFRSF9 axis. M2-TAMs, in turn, enhance WT malignancy by activating the PI3K/Akt pathway in tumor cells. These findings provide new potential biomarkers and therapeutic targets for WT diagnosis and treatment.